Pengembangan e-komik matematika berbasis etnomatematika betawi untuk meningkatkan literasi matematika siswa SMK - Nuraita, Nurjana; Suhendri, Huri; Mulyatna, Fauzi (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study aims to develop a mathematics e-comic based on Betawi ethnomathematics as an alternative instructional medium for tenth-grade vocational high school (SMK) students, thereby providing learning materials that are both contextual and engaging. Design/methodology/approach: Employing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), this research involved a limited trial across three vocational high schools. Data collection instruments encompassed needs analysis questionnaires, validation sheets from experts (subject matter, educational technology, and information technology), mathematics literacy tests, and response questionnaires from both teachers and students.Findings: The findings reveal that the e-comic medium falls into the